Role of the Millennial Generation in Conserving Mangrove and Cultural Heritage in Sanrobone, South Sulawesi - Rohani Ambo-Rappe; Ratnawati Gatta; Suriadi Mappangara; Marzuki Ukkas; Ahmad Faizal (Jurnal Penyuluhan, 2020)
Sanrobone is a coastal village with tourism potential, including cultural heritage sites and mangrove forests. However, most of the forests have been converted into fish ponds and seaweeds, resulting in abrasion that erodes the village and damages several historical sites in the area. The program aims to empower millennial generation in preserving the cultural reserves and mangrove forests, which in turn can become a community income sector. The millennial generation of Sanrobone is participating in repairing the Sanrobone Fort (Benteng), the Sanrobone King’s Graves, and the mangrove forests through the development of cultural and mangrove-based tourism. This outreach activity employed an active participatory method, namely: (1) Socialisation of the Culture and Mangrove Tourism concept to the community and local government; (2) Training in mangrove planting and management; (3) a comparative study trip to developed cultural tourism and mangrove-based tourism areas. The results showed the millennial awareness of the tourism potential of the region is getting higher, and they can already see various opportunities to manage these tourism potentials as a source of income. What needs to be done next is to improve the skills of the millennial generation in the promotion of regional tourism through digital marketing, which is needed for effective sustainable tourism development in the industrial era 4.0.